Digital Hindu Influencers and Contemporary Spiritual Discourse - Aiswarya S Nair (Asosiasi Khazanah Cendekia, 2026)
With the proliferation of cheap internet, smartphones, and government-funded digital initiatives, social media platforms have emerged as powerful areas for disseminating ideological as well as religious content. Hindu spiritual leaders, like Sadhguru, Devdutt Pattanaik, and Gaur Gopal Das, have capitalized on these platforms to propagate the Hindu philosophy in a renewed form, which intertwines self-help narratives and spiritual discourse. These “Hindu” influencers claim to democratize spiritual knowledge and offer accessible wisdom, but their digital presence simultaneously raises critical concerns regarding the commercialization of faith, algorithmic amplification of ideology, and the erasure of caste, gender, and class inequalities. This paper examines how these digital religious figures utilize social media to cultivate charismatic authority, build unidirectional relationships, and monetize spiritual content. It debriefs the implications of such trends for pluralism, religious identity, and public discourse in India. Furthermore, the study draws parallels with digital influencers in Christianity and Islam to locate Hindu digital spirituality within a global paradigm of online religious transformation. The paper also examines how digital Hinduism marginalizes embodied and erotic ways of knowing, especially those rooted in Bhakti and female devotion, in favour of sanitized spiritual performances.